THE EFFECT OF TEACHER PERSONALITY AND LEARNING MOTIVATION ON MATHEMATICAL LEARNING OUTCOMES OF SEASON STATE STUDENTS IN MAROS DISTRICT - Sahara, Rina Juanti (Sains Global Institut, 2019)
The purpose of this research is to know: (1) Influence of interaction between teacher's personality and student's learning motivation toward student's mathematics learning result of SMP Negeri in Maros, (2) Difference of mathematics learning result of student of SMP Negeri in Maros based on teacher personality type, (3) Difference of learning result of mathematics of student of SMP Negeri in Maros based on difference of learning motivation. This type of research is ex post facto research. Data were collected by questionnaire of teacher's personality, questionnaire of learning motivation and test of learning result that has been tested for its validity and reliability. Data analysis technique used is two way anava using computer program aid R. The result of hypothesis test of this research show. (i) There is no interaction between teacher personality and learning motivation toward mathematics learning outcomes of SMP Negeri in Maros, (ii) There is a difference of mathematics learning result of students of SMP Negeri in Maros based on personality type of teacher, where teacher extravertion personality is best and has highest average learning result score (iii) There is difference of mathematics learning result of students of SMP Negeri in Maros based on differences in motivation to learn, where it is found that high intrinsic learning motivation that gives the optimum effect and to improve learning outcomes then high intrinsic learning motivation that needs to be improved